Chromosome Numbers of Angiosperms in Tanzania - Gill, L.S.; S, F.L. (Tanzania Journal of Science, 1975)
Chromosome Numbers of 30 taxa of angiosperms from Tanzania are reported. Of these, counts of 8 species are new. The occurrence of B-chromosome in Ornithogalum longibracteatum is reported for the first time.